An Intrinsically Disordered Peptide Facilitates Non‐Endosomal Cell Entry. (2nd February 2016) - Medina, Scott H.; Miller, Stephen E.; Keim, Allison I.; Gorka, Alexander P.; Schnermann, Martin J.; Schneider, Joel P.
Abstract: Many cell‐penetrating peptides (CPPs) fold at cell surfaces, adopting α‐ or β‐structure that enable their intracellular transport. However, the same structural folds that facilitate cellular entry can also elicit potent membrane‐lytic activity, limiting their use in delivery applications. Further, a distinct CPP can enter cells through many mechanisms, often leading to endosomal entrapment. Herein, we describe an intrinsically disordered peptide (CLIP6) that exclusively employs non‐endosomal mechanisms to cross cellular membranes, while being remarkably biocompatible and serum‐stable. We show that a single anionic glutamate residue is responsible for maintaining the disordered bioactive state of the peptide, defines its mechanism of cellular entry, and is central to its biocompatibility. CLIP6 can deliver membrane‐impermeable cargo directly to the cytoplasm of cells, suggesting its broad utility for delivery of drug candidates limited by poor cell permeability and endosomal degradation.